L-Menthol-Loadable Electrospun Fibers of PMVEMA Anhydride for Topical Administration - Amalia Mira; Marta Rubio-Camacho; David Alarcón; Enrique Rodríguez-Cañas; Asia Fernández-Carvajal; Alberto Falco; Ricardo Mallavia (MDPI AG, 2021)
Poly(methyl vinyl ether-alt-maleic anhydride) (PMVEMA) of 119 and 139 molecular weights (P119 and P139, respectively) were electrospun to evaluate the resulting fibers as a topical delivery vehicle for (L-)menthol. Thus, electrospinning parameters were optimized for the production of uniform bead-free fibers from 12% w/w PMVEMA (±2.3% w/w menthol) solutions, and their morphology and size were characterized by field emission scanning electron microscopy (FESEM). The fibers of P119 (F119s) and P139 (F139s) showed average diameter sizes of approximately 534 and 664 nm, respectively, when unloaded, and 837 and 1369 nm when loaded with menthol. The morphology of all types of fibers was cylindrical except for F139s, which mostly displayed a double-ribbon-like shape. Gas chromatography-mass spectrometry (GC-MS) analysis determined that not only was the menthol encapsulation efficiency higher in F139s (92% versus 68% in F119s) but also that its stability over time was higher, given that in contrast with F119s, no significant losses in encapsulated menthol were detected in the F139s after 10 days post-production. Finally, in vitro biological assays showed no significant induction of cytotoxicity for any of the experimental fibers or in the full functionality of the encapsulated menthol, as it achieved equivalent free-menthol levels of activation of its specific receptor, the (human) transient receptor potential cation channel subfamily M (melastatin) member 8 (TRPM8).